Burden of non-communicable diseases attributable to dietary risks in Brazil, 1990-2019: an analysis of the Global Burden of Disease Study 2019 - Machado,Ísis Eloah (2022)
Abstract INTRODUCTION: An unhealthy diet is a modifiable risk factor for non-communicable diseases (NCDs), one of the most important public health problems in Brazil. This study aimed to analyze the burden of NCDs attributable to dietary risks in Brazil between 1990-2019. METHODS: Secondary data from the Global Burden of Disease Study were used to estimate the burden attributable to fifteen dietary risks in Brazil. The main sources of data for Brazil were national surveys and international databases. A comparative risk assessment was used to obtain the population attributable fraction. We described the intake of each dietary risk and the distribution of number and rates of deaths and Disability-adjusted life years (DALYs) attributable to diet by sex, age, state, and year from 1990-2019. RESULTS: Cardiovascular diseases, diabetes mellitus, and neoplasms were the main NCDs attributable to an unhealthy diet. Age-standardized mortality and DALYs rates attributable to unhealthy diet decreased between 1990-2019 (-51.5% and -48.8, respectively). Diet high in red meat and sodium, and low in whole grains were the three main risk factors contributing to the burden of NCDs both in 1990 and 2019. The burden of NCDs was higher among males in the middle-aged population (around 50 years), as well as in the states of Maranhão, Rio de Janeiro, and Alagoas. CONCLUSIONS: The present study found a suboptimum diet among the Brazilian population. The major contributors to this burden were diet high in red meat and sodium and low in whole grains. This study supports priorities in public policies on food and nutrition to reduce the burden of NCDs.